Exploring the Implementation of Carbon Tax Policy within the Framework of Sustainable Finance: Stakeholders' Perspectives - Zenever, Sisilia; Arifin, Firmansyah; Mikial, Msy; Hariyanto, Rudy (Universitas Islam Nahdlatul Ulama Jepara, 2025)
This study aims to understand the impact of Carbon Tax policy implementation on sustainable finance from a Stakeholder Perspective. The research employs a qualitative approach, using in-depth interviews and focus groups to gather insights from a diverse group of stakeholders, including government officials, corporate leaders, investors, and the general public. This study uncovers a range of perspectives on the effectiveness and challenges of carbon tax implementation on sustainable finance. Key factors influencing successful implementation include regulatory framework, stakeholder engagement, and market readiness. This study is limited by its qualitative approach, which may not capture the full range of perspectives across regions or sectors. This study contributes to the discourse on environmental policy and sustainable finance by providing insights into the practical challenges and opportunities in integrating carbon tax policy with sustainable finance. It offers valuable guidance for policymakers, industry leaders, and researchers in the field. The novelty of this study lies in its focus on the intersection of carbon tax policy and sustainable finance, offering a detailed exploration of stakeholder perspectives and highlighting practical implications for aligning environmental policy with financial sustainability goals.